No association between subclinical hypothyroidism and dyslipidemia in children and adolescents - Ashkan Habib; Asadollah Habib (BMC, 2020)
Abstract Background There are controversies about the correlation between higher levels of thyroid stimulating hormone (TSH) and dyslipidemia in children. This study was designed to assess the relation between lipid profile components and TSH levels in children. Method This cross-sectional study was performed in a pediatric endocrinology growth assessment clinic in Shiraz, southern Iran. Children aged 2-18 years who referred to the clinic from January until April 2018 were included. TSH levels equal or above 5 mIU/L and lower than 10 mIU/L with normal free T4 (FT4) were considered as having subclinical hypothyroidism (SH). Results Six hundred sixty-six children were euthyroid while 181 had SH. No significant difference was found between the mean serum total cholesterol (P = 0.713), LDL-C (P = 0.369), HDL-C (P = 0.211), non-HDL-C (P = 0.929), and triglyceride (P = 0.215) levels between euthyroid children and subjects with SH. There was also no significant difference in the prevalence of dyslipidemias in any lipid profile components between the two groups. The adjusted correlation was not significant between TSH levels and any lipid profile component. Conclusion Based on the results of our study, we found no correlation between SH and dyslipidemia in children. The association between dyslipidemia and SH in children still seems to be inconsistent based on the results of this and previous studies. We recommend a meta-analysis or a significantly larger retrospective study on this subject.